A Novel Approach to Well‐Aligned TiO2 Nanotube Arrays and Their Enhanced Photocatalytic Performances. Issue 6 (8th January 2013) - Zhang, Weixin; Chen, Gongde; Yang, Zeheng; Zeng, Chunyan
Abstract : A simple route has been developed to prepare well‐aligned TiO2 nanotube arrays, which is based on outward coating of TiO2 and inward etching of Cu(OH)2 nanorod templates. Effects of annealing temperature and time on the crystal size and crystallinity of TiO2 nanotube arrays and photocatalytic activities of TiO2 nanotube arrays for degradation of Rhodamine B in aqueous solution have been investigated. The results indicate that the TiO2 nanotube arrays annealed at 500°C for 2 h possessed an enhanced photocatalytic activity in comparison with the TiO2 nanotube arrays without post heating and commercial anatase TiO2 nanoparticle film and presented a good life cycle performance. Scale‐up of the process has also been demonstrated. Our work opens a new avenue to fabricate free‐standing TiO2 nanotube arrays and demonstrates an excellent photocatalytic performance of the anatase TiO2 nanotube arrays for wastewater treatment. © 2012 American Institute of Chemical Engineers AIChE J, 59: 2134–2144, 2013